PERENCANAAN PEMEKARAN KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Syahdan, Nur; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The Government Regulation No. 19 of 2008 concerning the District, has been given the opportunity and guidance for a regency / city who wish to form a sub-district or sub-district devide into several districts, if it has met the requirements of the administrative, technical and physical territoriality. Bengkalis is one of the largest districts in Riau have attempted expansion planning district that is currently in the process of approval of the central government and the Province.The concept of theories used by researchers is the theory Dervish concept consists of Planning, Objectives, Policies, Procedures, the progress of the program. This study uses qualitative research with an assessment of descriptive data. In collecting the data, the authors use the technique of interview, observation and documentation.Researchers used the method in this research is descriptive qualitative, the source of the data used in this study include primary and secondary data, the location of this research is in the district of Bukit Batu Bengkalis. Informen in this study is the Parliament, Expansion Team, Head, Head of the village, and the people concerned.The results of this study indicate that the planning division of Bukit Batu Bengkalis districts already implemented through several processes and requirements for expansion in accordance with Government Regulation No. 19 of 2008, but once the planning division is influenced by several factors. Factors that influence the planning division of districts, among others, human resources, then the time factor and political factors.Keywords: Planning, Expansion, District